ผลของการใช้การวางแผนจำหน่ายผู้ป่วยเด็กโรคปอดอักเสบต่อการกลับมารักษาซ้ำของผู้ป่วยเด็กโรคปอดอักเสบและความพึงพอใจของผู้ดูแล สถาบันสุขภาพเด็กแห่งชาติมหาราชินี - นิภาพร หลีกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
The purposes of this quasi experimental research were to study theeffects of using a discharge planning on the readmission rate of children withpneumonia and also to determine caregivers’ satisfaction with nursing services atQueen Sirikit National Institute of Child Health. The research subjects consisted of30 caregivers who care of children with pneumonia .The subjects were assignedto either the experimental group or control group. The research instruments werethe training workshop project , the training workshop program, clinical nursingpractice guidelines for children with pneumonia , handbooks for caregivers whocare for children with pneumonia, observation forms of nursing practice anddischarge planning handbooks for nurses.The data collection instruments werereadmission records, and questionnaires of caregivers’ satisfaction with nursingservices,The Instruments were tested for content validity by five experts, and thevalidity was .86 The Cronbach’s alpha coefficients were .91 Statistical methodsused in the data analysis were percentage, mean, median, and Mann –Whitney Utest.The research findings were as follows:1. The readmission rate of children with pneumonia in both groups wasnot significantly different.2. Caregivers’satisfaction with nursing service in the experimental groupwas significantly higher than the control group.(p<.05).